PENERAPAN MODEL THINK TALK WRITE UNTUK MENINGKATKAN KETERAMPILAN SISWA DALAM MENULIS KARANGAN DESKRIPSI DI SEKOLAH DASAR - Panji Maulana; MT Hartono Ikhsan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2018)
The problem in this study was the low learning activities and writing skills of fourth grade students of Cimanggung Elementary School in Cimanggung District, Sumedang Regency. This study aims to determine the increase in student learning activities, teacher teaching activities, and writing essay writing skills of class IV students using the Think Talk Write model. The instruments used in this study are observation sheets of student learning activities, teacher activity observation sheets, and tests. The purpose of this study is to improve the ability to write essays and student learning activities, describe the steps and processes / implementation of writing essay learning by applying the model TTW (Think Talk Write) learning, and describe whether there is an increase in the ability to write essays by applying the TTW (Think Talk Write) learning model to fourth grade students of Cimanggung Elementary School in Cimanggung District, Sumedang Regency. The research method used is PTK (Class Action Research) with the research design used refers to the model developed by Kemmis and Taggart, namely a spiral model that begins with: 1) planning (planning); 2) action / action (acting); 3) observation (observing); and 4) reflection (reflecting). The research subjects were 30th grade students at SDN Cimanggung, consisting of 15 women and 15 men. This study was conducted for 2 cycles. The results of the study are, 1) The use of think talk write model can improve student learning activities in writing description essays, 2) The use of think talk write models can also increase teacher activities, and 3) Use of think talk write models can also improve student learning outcomes in writing essay description. Masalah dalam penelitian ini adalah rendahnya aktivitas belajar dan keterampilan menulis siswa kelas IV SDN Cimanggung Kecamatan Cimanggung Kabupaten Sumedang. Penelitian ini bertujuan untuk mengetahui peningkatan aktivitas belajar siswa, aktivitas mengajar guru, dan keterampilan menulis karangan deskripsi siswa kelas IV dengan menggunakan model Think Talk Write. Adapun instrumen yang digunakan dalam penelitian ini adalah lembar observasi aktivitas belajar siswa, lembar observasi aktivitas guru, dan tes .Tujuan penelitian ini yaitu untuk meningkatkan kemampuan menulis karangan dan aktivitas belajar siswa, mendeskripsikan langkah-langkah dan proses/pelaksanaan pembelajaran menulis karangan dengan menerapkan model pembelajaran TTW (Think Talk Write), dan mendeskripsikan ada tidaknya peningkatan kemampuan menulis karangan dengan menerapkan model pembelajaran TTW (Think Talk Write) pada siswa kelas IV SDN Cimanggung Kecamatan Cimanggung Kabupaten Sumedang. Metode penelitian yang digunakan adalah PTK (Penelitian Tindakan Kelas) dengan desain penelitian yang digunakan mengacu kepada model yang dikembangkan oleh Kemmis dan Taggart, yaitu model spiral yang dimulai dengan : 1) perencanaan (planning); 2) aksi/tindakan (acting); 3) observasi (observing); dan 4) refleksi (reflecting). Subjek penelitian adalah siswa kelas IV SDN Cimanggung yang berjumlah 30 orang, terdiri dari 15 orang perempuan dan 15 orang laki-laki. Penelitian ini dilakukan selama 2 siklus. Hasil penelitian yaitu, 1) Penggunaan model think talk write dapat meningkatkan aktivitas belajar siswa dalam menulis karangan deskripsi, 2) Penggunaan model think talk write juga dapat meningkatkan aktivitas guru, dan 3) Penggunaan model think talk write juga dapat meningkatkan hasil belajar siswa dalam menulis karangan deskripsi.